IMPLEMENTASI BIMBINGAN BELAJAR DAN PENANAMAN NILAI-NILAI KEARIFAN LOKAL PADA TRADISI BATIK GUNA MEWUJUDKAN CIVIS DISPOSITION GENERASI MUDA DI DESA GUNUNGSARI KECAMATAN BUMIAJI KOTA BATU - Susandi Susandi; Emil Kholif Maulida Azizah; Grace Debora Marcheline Afiq; Naudy Dian Ayu Saputri; Muhammad Rizal Laksono (JPM PAMBUDI, 2022)
Potential-based community service (PMBP) is one of the important activities for the academic community as academic functional staff to develop knowledge, skills, and solve problems. This community service aims to provide education to the community about the importance of education, skills, and environmental stewardship. Individual potential-based community service activities (PMBP) of IKIP Budi Utomo Malang were carried out in Gunungsari Village, Pegergunung Hamlet and Claket Hamlet, Bumiaji Distriet, Batu City. This service activity is carried out from February 1 to March 31, 2022. This activity certainly has an impact on change for the village, where the results can be obtained, namely increasing learning development and being able to make products with their own hands that can be used as tablecloths. The result of this community service is an increase in knowledge, understanding, and awareness of education and the environment. However, this program cannot be carried out continuously due to time constraints in the implementation of PMBP. Therefore, we feel that this program is very good and needs to be followed up by the IKIP BUDI UTOMO MALANG campus